Dry Carbonate Sorbents for CO2 Capture from Flue Gases: Role of Support in Adsorption Efficiency and Thermal Stability - Bolatbek Khussain; Alexandr Sass; Alexandr Brodskiy; Murat Zhurinov; Ivan Torlopov; Kenzhegul Rakhmetova; Daulet Zhumadullaev; Yerzhan Boleubayev; Atabek Khussain; Abzal Kenessary; Adel Sarsenova; Tumen Darzhokov (Molecules)
This study presents the results of an investigation of carbonate-containing sorbents for CO2 capture with natural support materials—kaolin and calcium carbonate—at various loadings of the active phase of Na2CO3. The effects of the support type on the distribution of the active component, phase composition, and pore structure of the sorbents were studied. It was found that a Na2CO3 loading of 25 wt.% provides the best balance between sorption capacity and technological feasibility. The thermal stability and regeneration capacity of the sorbents were evaluated under high-temperature conditions, revealing high thermal stability of the Na2CO3/CaCO3 system up to 1000 °C, along with its durability over multiple adsorption–desorption cycles. Kinetic studies on the Na2CO3/CaCO3 sorbent using the shrinking core model demonstrated that the overall CO2 chemisorption process is controlled by surface chemical reaction at temperatures below 50 °C. The obtained results demonstrate the high potential of CaCO3-based sorbents for practical applications in low-temperature CO2 capture technologies. A promising direction for the use of such sorbents within CCUS is the development of integrated systems, where CO2 capture is combined with its conversion into valuable products (e.g., methane, methanol, formic acid) through catalytic processes.